About the reaction at the robot leg - Huyen, Pham; Mau, Nguyen Thanh (Vietnam Journal of Mechanics, 1993)
In this paper the authors studies the robot reaction using the new controllable method of walking robot. The result gives us the most optimal motion for robot.